A framework to model the STPA hierarchical control structure of an autonomous ship - Chaal, Meriam; Valdez Banda, Osiris A.; Glomsrud, Jon Arne; Basnet, Sunil; Hirdaris, Spyros; Kujala, Pentti (Safety science, 2020)
•A framework to model a hierarchical control structure for the STPA analysis of an autonomous ship is presented.•STAMP, STPA and STECA were used as the foundation of the proposed framework.•The framework makes use of the available knowledge of current shipping operation and seafarers experience.•The resulting control structure of shipping operation includes the autonomous ship and the Shore-based Control Centre as controlled processes.•The application to the Autonomous Navigation System reveals substantial information for the safety of autonomous ships. The demand for risk and safety analysis is becoming greater due to the increased complexity of modern systems such as autonomous ships. Safety is one of the main motivations behind the efforts of multiple organizations to develop autonomous ships. The adoption of an early system-theoretic approach to safety such as System Theoretic Process Analysis (STPA) is an effective way to integrate safety in complex systems. Furthermore, many authors have urged the use of this method to analyse the risks of autonomous vessels in the development phases. Applying STPA requires a description of the system to model the hierarchical control structure and conduct the analysis. At this stage, the functional description of autonomous ships remains limited, which poses a challenge in building the hierarchical control structure. This paper proposes a framework for developing a hierarchical control structure of an autonomous ship. The framework is founded on the principles of the STPA control structure and its five main elements. It makes use of the current shipping operation system, the available information about autonomous ships and the experience of seafarers executing diverse tasks on-board conventional ships. The application of the framework showed that the information provided by the seafarers is essential in developing an initial functional description of an autonomous ship. Furthermore, the results revealed that in addition to the technical aspects of autonomous ships, introducing these vessels into the organizational control structure of current maritime operation also poses challenges that need to be addressed in the earliest design phase.